EFFECTIVE METHODS FOR INCREASING STUDENT MOTIVATION IN ENGLISH LANGUAGE TEACHING (American Journal of Technology and Applied Sciences, 2026)
This article is devoted to studying effective methods of increasing student motivation in English language teaching. The article analyzes the concept of motivation, its significance in the educational process, as well as interactive and innovative methods applied in practical lessons. The research results are aimed at enhancing student participation, increasing interest in learning, and improving language acquisition efficiency.